Crosstalk of Alzheimer’s disease-phenotype, HPA axis, splenic oxidative stress and frailty in late-stages of dementia, with special concerns on the effects of social isolation: A translational neuroscience approach - Muntsant, Aida; Giménez-Llort, Lydia (Frontiers in Aging Neuroscience, 2022)
Coping with emotional stressors strongly impacts older people due to their age-related impaired neuroendocrine and immune systems. Elevated cortisol levels seem to be associated with an increased risk of cognitive decline and dementia. In Alzheimer’s disease (AD), alterations in the innate immune system result in crosstalk between immune mediators and neuronal and endocrine functions. Besides, neuropsychiatric symptoms such as depression, anxiety, or agitation are observed in most patients. Here, we studied the psychophysiological response to intrinsic (AD-phenotype) and extrinsic (anxiogenic tests) stress factors and their relation to liver, kidneys, heart, and spleen oxidative status in 18-months-old female gold-standard C57BL/6 mice and 3xTg-AD mice model for AD. The emotional, cognitive, and motor phenotypes were assessed under three different anxiogenic conditions. Survival, frailty index, and immunoendocrine status (corticosterone levels and oxidative stress of peripheral organs) were evaluated. Genotype differences in neuropsychiatric-like profiles and cognitive disfunction in 3xTg-AD females that survived beyond advanced stages of the disease persisted despite losing other behavioral and hypothalamic–pituitary–adrenal (HPA) physiological differences. A secondary analysis studied the impact of social isolation, naturally occurring in 3xTg-AD mice due to the death of cage mates. One month of isolation modified hyperactivity and neophobia patterns and disrupt the obsessive-compulsive disorder-like digging ethogram. Frailty index correlated with spleen organometrics in all groups, whereas two AD-specific salient functional correlations were identified: (1) Levels of corticosterone with worse performance in the T-maze, (2) and with a lower splenic GPx antioxidant enzymatic activity, which may suppose a potent risk of morbidity and mortality in AD.